Development of Higher Order Thinking Skill-based Test in Mathematics Learning - Abdullah, Riyan (Jurnal Pendidikan Profesi Guru, 2024)
Human thinking abilities in the world of education are generally categorized into two parts, namely the ability to think critically and the ability to think creatively, both of which are included in high-level thinking abilities. This research aims to develop a Higher Order Thinking Skill-based question instrument in mathematics learning. The method involves development studies using Tessmer's Formative Research Design model. This research involved experts from academics and mathematics practitioners as well as class X Madrasah Aliyah Negeri 1 Pohuwato. Data was obtained from the description test and analyzed to measure the validity, reliability, level of difficulty, and distinguishing power of the instrument. The results showed that of the 60 class further to poor higher level thinking abilities. Even though there are no students with very good high-level thinking abilities, the average high-level thinking ability of all class X students at Madrasah Aliyah Negeri 1 Pohuwato is 57.38, indicating that the test instrument is effective. The Higher Order Thinking Skills description test questions that were tested had high validity and reliability, as well as a good level of difficulty and differentiating ability of the questions, making this test instrument suitable for evaluating students' higher order thinking abilities